"Modes of mediation" for conceptualizing how different roles for accountants are made present. Issue 3 (3rd August 2015) - El-Sayed, Heba; Youssef, Mayada Abd El-Aziz
Abstract : Purpose: – This paper aims to, using the concept of "modes of mediation", examine how different roles for accountants are "made present" in an Egyptian manufacturing company. The paper introduces the notion of "modes of mediation" as a different perspective for the opposing popular archetypes of accountants: "bean-counter" versus "business partner". Modes of mediation emphasise the materiality of artefacts, entities and technologies, as well as organisational space and spatial settings. Design/methodology/approach: – The paper draws on a field study in an Egyptian manufacturing company where accountants are engaged as business partners and involved in operations planning and decision-making. The data were collected over a period of four years through participant observation, interviews and ethnographic techniques. Findings: – The paper reveals the relational nature of accountants' calculative agency and shows how roles of accountants are intimately associated with a web of technologies and artefacts, as well as spatial working arrangements that represent particular "modes of mediation". Research limitations/implications: – The concept of "modes of mediation", which is still under-explored in the role change literature, is useful in studying the roles of accountants. It enriches our understanding of the wider involvement of accountants in business decision-making that goes beyond the major drivers of role change and deliberate interventions discussed in the existing literature. Originality/value: – The paper contributes to the literature on role change by drawing attention to the way in which different modes of mediation, involving certain material and spatial arrangements, enact different forms of calculative agency. Minor alteration to these arrangements can result in a wider involvement of accountants in business decision-making.